Design for privacy in ubiquitous computing environments - Bellotti, Victoria; Sellen, Abigail (Proceedings of the European Conference on Computer Supported Cooperative Work (ECSCW), Milan, Italy, Sept. 13-17., 1993)
Current developments in information technology are leading to increasing capture and storage of information about people and their activities. This raises serious issues about the preservation of privacy. In this paper we examine why these issues are particularly important in the introduction of ubiquitous computing technology into the working environment. Certain problems with privacy are closely related to the ways in which the technology attenuates natural mechanisms of feedback and control over information released. We describe a framework for design for privacy in ubiquitous computing environments and conclude with an example of its application.